A Systematic Review of Consumer Perceptions of Smart Packaging Technologies for Food - Young, Erin; Mirosa, Miranda; Bremer, Phil (Frontiers in Sustainable Food Systems, 2020)
Smart packaging, an emerging technology in the food packaging industry incorporates both active and intelligent technologies. Consumer demand for natural products and increasingly extended and diverse supply chains required to feed the growing global population, mean that traditional packaging is becoming less capable of meeting the functional demands placed on it. To help ensure the commercial success of proposed smart packaging technologies a thorough understanding of consumers attitudes toward them is required. Understanding the cultural, social and cognitive factors that affect acceptance will help “fine tune” smart packaging development to best meet consumer preferences and needs and ensure that communication about the technologies effectively addresses consumer concerns and educates them on the benefits. This systematic review of 28 peer reviewed journal articles summarizes the current knowledge on consumer acceptance or rejection of active and intelligent packaging, and the behavioral forces behind those attitudes. Articles containing primary data and published in the English language over the last 10 years reporting consumer responses to active and/or intelligent packaging technologies in general or to more specific technologies that achieved the functional goals of active or intelligent packaging were obtained and analyzed for themes in the qualitative data analysis software NVivo. Themes were organized into groups as to whether they identified control variables, moderating variables, barriers or motivations to purchase and the benefits of the technology. To develop a conceptual framework for understanding consumer preferences for smart packaging, the identified themes were integrated with several consumer behavior models including the theory of planned behavior and an attitude model. Consumer perceptions of smart packaging is a poorly covered research area with most research being clustered in Europe and a smaller cluster in the Americas so there were significant opportunities to build on the body of knowledge.